2023
DOI: 10.21203/rs.3.rs-2182817/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MSCs’ conditioned media cytokine and growth factor profiles and their impact on macrophage polarization

Abstract: Background. There is a growing body of evidence that multipotent mesenchymal stromal cells’ (MSCs’) remarkable therapeutic potential is attributed not only to their differentiation and regenerative capacity, but also to the paracrine effect, underlying their immunomodulatory properties. MSCs’ secretome (i.e., cytokines, growth factors, and extracellular vesicles) is therefore increasingly discussed in the context of their ability to modulate inflammatory response and promote regeneration. There is evidence th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…While the secretome of MSC-EVs has shown to have high levels of IL-6 and IL-8 (27), a recent study showed that the conditioned media derived from umbilical cord (UC)-MSC promoted anti-inflammatory macrophages polarization. This despite a mostly proinflammatory profile of cytokines, though the authors have only investigated surface markers of M2 macrophages (28). MSC-EVs contain nucleic acids, which may bind to TLR7 and 9 as foreign nucleic acids and trigger a pro-inflammatory cascade.…”
Section: Multiparametric Influence On the Immunomodulatory Potential ...mentioning
confidence: 99%
“…While the secretome of MSC-EVs has shown to have high levels of IL-6 and IL-8 (27), a recent study showed that the conditioned media derived from umbilical cord (UC)-MSC promoted anti-inflammatory macrophages polarization. This despite a mostly proinflammatory profile of cytokines, though the authors have only investigated surface markers of M2 macrophages (28). MSC-EVs contain nucleic acids, which may bind to TLR7 and 9 as foreign nucleic acids and trigger a pro-inflammatory cascade.…”
Section: Multiparametric Influence On the Immunomodulatory Potential ...mentioning
confidence: 99%
“…The polarization of macrophages from M1 to M2 phenotype was assessed by staining the cells with fluorochrome-conjugated anti-CD206 (BD Biosciences, USA) followed by fixation and permeabilization of the cells using an Intra Prep Permeabilization kit (Beckmann Coulter, USA) for intracellular staining. Further, the cells were stained with iNOS (Thermo Fisher Scientific, USA), CD68, and Arginase-1 (BD Biosciences, USA) for 30 minutes at room temperature and the cells were acquired using a DxFlex flow cytometer (Beckmann Coulter) to enumerate the M1 and M2 macrophages (31).…”
Section: Macrophage Polarizationmentioning
confidence: 99%